Od przetrwania do budowania kompetencji studentów. Analiza zmian w wybranej szkole niepublicznej - Ratajczak, Sabina (From the survival to the creation of students' competence. The analysis of changes in a chosen non-public school, 2006)
The aim of this article is the attempt to indicate crucial challenges for contemporary University education. Objects of analyses are instructions, formulated in Polish literature, about postulated changes in methods of students' education and changes occurring at the Academy of Business in Dąbrowa Gornicza. The article is concentrated on three kinds of challenges: relation: student - school, forms and content of teaching
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 286-295